(untitled) (Revista de Investigaciones Universidad del Quindío, 2010)
The essential oil from Lippia origanoides H.B.K. was extracted using two techniques, Microwave Assisted Hydrodistillation (MWHD) and Steam Distillation apparatus (SV), with optimal operation times of 60 and 90 minutes respectively, giving better yield rate for MWHD, with leaves in the dry state. The analyses of the essential oil by Gases Chromatography coupled with Mass Detector showed that majority compound was Thymol. The antimicrobial activity of essential oil was evaluated in Gram–positive and Gram–negative bacteria, filamentous fungus and yeast, using different concentrations of oil, in V/V percentage with 98% ethanol. The antimicrobial action was greaterin the Gram-positive and fungus and yeast microorganism.